2020
DOI: 10.1200/po.19.00330
|View full text |Cite
|
Sign up to set email alerts
|

CES2 Expression in Pancreatic Adenocarcinoma Is Predictive of Response to Irinotecan and Is Associated With Type 2 Diabetes

Abstract: PURPOSE The combination chemotherapy of fluorouracil, leucovorin, irinotecan, and oxaliplatin (FOLFIRINOX) has provided clinically meaningful improvement for pancreatic ductal adenocarcinoma (PDAC). We previously uncovered a role for the serine hydrolase carboxylesterase 2 (CES2) in mediating intratumoral activation of the prodrug irinotecan, a constituent of FOLFIRINOX. We aimed to further test the predictive value of CES2 for response to irinotecan using patient-derived xenograft (PDX) models and to elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Animal experiment protocols were reviewed and approved by The University of Texas MD Anderson Cancer Center IRB and in accordance with the Guidelines for the Care and Use of Laboratory Animals published by the NIH (Bethesda, MD). Detailed information regarding patient-derived xenografts (PDXs) is described in a prior publication [ 15 ]. For orthotopic xenograft models of PDAC and in vivo imaging, an enhanced GFP/firefly luciferase double-expressing cassette FG12 was introduced into AsPC-1 shCES2 or scramble control cells by lentiviral infection, as described previously [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal experiment protocols were reviewed and approved by The University of Texas MD Anderson Cancer Center IRB and in accordance with the Guidelines for the Care and Use of Laboratory Animals published by the NIH (Bethesda, MD). Detailed information regarding patient-derived xenografts (PDXs) is described in a prior publication [ 15 ]. For orthotopic xenograft models of PDAC and in vivo imaging, an enhanced GFP/firefly luciferase double-expressing cassette FG12 was introduced into AsPC-1 shCES2 or scramble control cells by lentiviral infection, as described previously [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The intrinsic role of CES2 in regulating lipid metabolism has been investigated in diabetes, liver steatosis, and nonalcoholic fatty liver disease [ [7] , [8] , [9] , [10] ]. To date, the relevance of CES2 in cancer has primarily been considered with respect to its functional role in mediating the activation of pro-drugs irinotecan and LY2334737 into their respective active forms [ 4 , 5 , [11] , [12] , [13] , [14] ], thereby providing a potential marker for predicting patient response to irinotecan- or LY2334737-containing regimens [ 2 , 5 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings highlight that the presence of T2DM before the start of neoadjuvant chemotherapy as well as the dynamic of HbA1c levels during the treatment are markers for response to FOLFIRINOX. In line with this, another independent clinical investigation demonstrated that elevated HbA1c levels can be utilized as a marker for stratifying patients most likely to respond to FOLFIRINOX 51 .…”
Section: Induction Of Anti-tumor Immunity By Increasing the Number Of Tumor-infiltrating T Cells Is Anmentioning
confidence: 73%
“…While FOLFIRINOX is more effective than gemcitabine, the regimen also causes more side effects and significantly reduces quality of life of patients. However, response to chemotherapy varies, with only one third of patients responding to a specific regimen 51 . Given the fact that patients with unresponsiveness to neoadjuvant chemotherapy and irresectable PDA have a median life expectancy of less than a year preventing FOLFIRINOX-induced toxicity is an urgent clinical need.…”
Section: Induction Of Anti-tumor Immunity By Increasing the Number Of Tumor-infiltrating T Cells Is Anmentioning
confidence: 99%
“…Serine hydrolase carboxylesterase 2 (CES2) is predictive of response to irinotecan as mediates its intra-tumoral activation. It is associated with type 2 diabetes [ 6 ].…”
Section: Pancreatic Cancermentioning
confidence: 99%